PENGAMATAN KADAR LOGAM BERAT MERKURI (Hg) DAN TEMBAGA (Cu) PADA DAGING IKAN DI TELUK KAO, HALMAHERA - Edward Edward (Jurnal Pro-Life, 2019)
Fish is sources of protein, minerals, vitamins, and polyunsaturated omega-3 fatty acids, which are considered beneficial for health. The purpose of this research was to analysize the levels of mercury (Hg) and copper (Cu) in several species of fish that live in Kao Bay, Halmahera. This research were carried out in November 2015. Fishes samples analyzed were suo fish (Sphyraena jello), tatameri (Gazza minuta), gaca (Lutjanus argentimaculatus), totodi (Synodus foetens) bubara (Caranx sp), ngafi (Stolephorus indicus) dan biji nangka (Upeneus vittatus). All samples was analyzed using Atomic Absorption Spectrophotometer (AAS). The results showed that the Hg levels is still in accordance with the safe treshold value set by the Indonesian National Standard (SNI) (2009), while Cu has passes the criteria set by the that SNI for seafood. Keywords: Teluk Kao, fishes, heavy metals of Hg and Cu